AN ANALYSIS OF SUBTITLING STRATEGIES IN THE INDONESIAN FILM "RUMAH DARA" - Budiarti, Meli (2017)
This research attempts to explore kinds of subtitling strategies, the most-frequently strategies found, and the contribution of the most-frequently strategies found in an Indonesian film Rumah Dara. In conducting the analysis, the research uses a theoretical framework of subtitling strategy proposed by Gotlieb (1994). In terms of its approach, this research belongs to descriptive approach. The data are in the forms of transcripts of the film Rumah Dara. The transcripts consist of 651 dialogues. This research shows that the most-frequently found strategy is transfer (42.55%). It is then followed by imitation (14.44%), condensation (11.21%), and paraphrase (10.91%). Therefore, the results of this research are expected to contribute to the improvement of translational quality in Indonesian films. In addition, it enriches the study of subtitling analysis in Indonesian thriller film.;--- Penelitian ini mencoba untuk mengeksplorasi jenis strategi penerjemahan, strategi yang paling sering ditemukan, dan kontribusi dari strategi yang paling sering ditemukan dalam film Indonesia Rumah Dara. Dalam melakukan analisis, penelitian ini menggunakan kerangka teori strategi penerjemahan yang diusulkan oleh Gotlieb (1994). Dalam hal pendekatan, penelitian ini menggunakan pendekatan deskriptif. Data yang dianalisis berbentuk transkrip film Rumah Dara. Transkrip tersebut terdiri dari 651 dialog. Penelitian ini menunjukkan bahwa strategi yang paling-sering ditemukan adalah transfer (42,55%). Kemudian diikuti oleh imitasi (14,44%), kondensasi (11,21%), dan parafrase (10,91%). Lebih lanjut, hasil penelitian ini diharapkan dapat memberikan kontribusi terhadap peningkatan kualitas penerjemahan dalam film Indonesia. Selain itu, penelitian ini dapat memperkaya studi analisis penerjemahan dalam film Indonesia dengan aliran thriller.